2020
DOI: 10.25046/aj050677
|View full text |Cite
|
Sign up to set email alerts
|

Burnout Among Primary School Teachers in the Wazzane Region in Morocco: Prevalence and Risk Factors

Abstract: Introduction: Burnout is a real malaise that affects the mental health of teachers. The objective is to determine the prevalence of burnout among primary school teachers in the Wazzane region and to look for associated risk factors. Methods: Descriptive crosssectional study conducted in 2017-2018 with a sample of 330 teachers. Socio-demographic and work-related data were assessed by a self-administered questionnaire and the Karasek Job Content Questionnaire (JCQ) the Karasek, the burnout by the Maslach Burnout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 19 publications
2
2
1
Order By: Relevance
“…Furthermore, student demotivation was a predictor of WRB in the current study, which is consistent with previous studies conducted in the USA (Aloe et al, 2014) and Morocco (Amri et al, 2021). Student demotivation problems disrupt the teaching-learning process or interfere with the orderly operation of the classroom, so teachers spend a considerable amount of time and energy dealing with student's disruptive behavior, so this can cause anger and frustration for teachers, these repeated experiences of frustration and anger in response to students lead to WRB (Aloe et al, 2014).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Furthermore, student demotivation was a predictor of WRB in the current study, which is consistent with previous studies conducted in the USA (Aloe et al, 2014) and Morocco (Amri et al, 2021). Student demotivation problems disrupt the teaching-learning process or interfere with the orderly operation of the classroom, so teachers spend a considerable amount of time and energy dealing with student's disruptive behavior, so this can cause anger and frustration for teachers, these repeated experiences of frustration and anger in response to students lead to WRB (Aloe et al, 2014).…”
Section: Discussionsupporting
confidence: 93%
“…The result of our study showed that job demand was significantly associated with WRB. This is consistent with findings from Sweden ( Arvidsson et al, 2019 ), Indonesia ( Ramdan et al, 2020 ), and Morocco ( Amri et al, 2021 ). A possible explanation could be that an increase in high job demands and work tasks may lead to increased time pressure, and less freedom to determine how work is carried out may contribute to increased WRB ( Arvidsson et al, 2019 ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations